Kinerja Keuangan sebagai Faktor Penentu dalam Meningkatkan Nilai Perusahaan Melalui Pengolahan Rasio Likuiditas, Solvabilitas, dan Aktivitas - Aura Annida Husna; Ana Kadarningsih (MANAJEMEN, 2025)
This study examines the impact of liquidity, solvency and activity on company value through the mediation of financial performance in Food and Baerage Companies on the Indonesia Stock Exchange (BEI) in 2021-2023. This study examines 70 out of 95 companies, analiyzing 210 financial records over a three-year period, with WarPLS 8.0. The approach applied is quantitative with data obtained from www.idx.co.id. The findings reveal that CR and TATO have significant impact on ROA, whereas DER does not. In addition, DER and TATO have a significant effect on PBV, but CR and ROA do not. This model describes the relationship between CR, DER, and TATO on PBV through ROA mediation.